Percentage of subcutaneous fatty tissue as an indicator of the physical status of volleyball players - Ratko Pavlovič; Vladan Savič; Nikola Radulovič (Matej Bel University, 2021)
Subcutaneous adipose tissue (skin folds) is a disruptive factor in many sports that overcome the force of gravity, including volleyball. In the field of volleyball, it is imperative to identify the anthropometric constitution, where the amount of subcutaneous adipose tissue plays a significant role. The study included 18 active players of the women's volleyball club Jahorina from Pale (BH=173±8.77cm;BW=66.04±9.09kg; BMI=22.03±2.19kg/m2, age=19.11±2.63), a member of the volleyball Premier League of Bosnia and Herzegovina with the main goal to analyze and determine the percentage of adipose fat as an indicator of physical status. Yuhasz skinfold test (Biceps skinfold, Triceps skinfold, Subscapular skinfold, Suprailiac skinfold, Abdomen skinfold, Front thigh skinfold, Rear thigh skinfold) was applied to assess skin folds. Measurements were performed with a skin fat measuring instrument (Caliper GIMA-model Plicometro, Italy) in accordance with the ISAK protocol. Statistical data processing included central and dispersion parameters and Pearson's correlation coefficients. Based on the obtained results, it can be concluded that 30% of significant ICC p<,05;p<0,01;p<0,001 were achieved. The percentage of skin folds of Jahorina volleyball players in body weight is 16.16% (12 kg), and body fat mass is 54.04 kg. Based on the obtained results, the amount of adipose tissue can be concluded that our sample is within the allowed values recommended for this population, and that amount is lower compared to previous research. DOI: https://doi.org/10.24040/sjss.2021.7.1.64-74